PEMANFAATAN POJOK BACA SEKOLAH DALAM MENINGKATKAN LITERASI MEMBACA SISWADI DESA SUNGAI TERAP - Nurul Annisa Dewantari Nasution; Suprihatin; Anggun Futri Sulanda; Amir Fauzan; Abdul Haris Al-Kahfi; Puspita Sari (STKIP Subang, 2025)
The low level of reading literacy among elementary school students in Sungai Terap Village is a significant issue that requires serious attention. Limited reading interest, inadequate literacy facilities, and lack of innovative learning methods are the main contributing factors. This Community Service Program (PKM) aims to improve students’ reading literacy through the utilization of school reading corners using a play-based learning method. This approach was chosen to create a fun, interactive, and child-friendly learning environment. The program was implemented through planning, implementation, and evaluation stages involving active participation from teachers and students. The results indicate an increase in students’ reading interest, active engagement, and reading comprehension skills. Therefore, the play-based reading corner approach is proven effective in enhancing reading literacy among students in Sungai Terap Village and can serve as a sustainable literacy development model in schools.